Microflora of processed cheese and the factors affecting it - Buňková, Leona; Buňka, František (Critical reviews in food science and nutriton, 2017)
The basic raw materials for the production of processed cheese are natural cheese which is treated by heat with the addition of emulsifying salts. From a point of view of the melting temperatures used (and the pH-value of the product), the course of processed cheese production can be considered "pasteurisation of cheese." During the melting process, the majority of vegetative forms of microorganisms, including bacteria of the family Enterobacteriaceae, are inactivated. The melting temperatures are not sufficient to kill the endospores, which survive the process but are often weakened. From a microbiological point of view, the biggest contamination problem of processed cheese is caused by gram-positive spore-forming rod-shaped bacteria of the genera Bacillus, Geobacillus, and Clostridium. Other factors affecting the shelf-life and quality of processed cheese are mainly the microbiological quality of the raw materials used, strict hygienic conditions during the manufacturing process as well as the type of packaging materials and storage conditions. The quality of processed cheese is not only dependent on the ingredients used but also on other parameters such as the value of water activity of the processed cheese, its pH-value, the presence of salts and emulsifying salts and the amount of fat in the product.
Keywords: grampozitivní bakterie; manipulace s potravinami; houby; sýr; Food Handling; potravinářská mikrobiologie; gramnegativní bakterie; Food Microbiology; Fungi; Gram-Positive Bacteria; Gram-Negative Bacteria; Cheese